2020
DOI: 10.1007/s00125-020-05112-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved oral hygiene is associated with decreased risk of new-onset diabetes: a nationwide population-based cohort study

Abstract: Aims/hypothesis Inflammation plays an important role in the development of diabetes, a major global health problem. Periodontal disease is also common in the general population. Because periodontal disease and poor oral hygiene can provoke transient bacteraemia and systemic inflammation, we hypothesised that periodontal disease and oral hygiene indicators would be associated with the occurrence of new-onset diabetes. Methods In this study we analysed data collected between 2003 and 2006 on 188,013 subjects fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 43 publications
(53 reference statements)
0
70
1
Order By: Relevance
“…Our findings support the negative association between MF and diabetes, as reported by Yamazaki et al [ 17 ]. A previous longitudinal study reported that the number of missing teeth (≥15 teeth) was positively associated with the occurrence of new-onset diabetes (hazard ratio = 1.21; 95% CI, 1.09–1.33) among 188,013 Korean adults [ 26 ]. This was consistent with our findings that individuals with an increasing number of remaining teeth tended to have lower odds of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support the negative association between MF and diabetes, as reported by Yamazaki et al [ 17 ]. A previous longitudinal study reported that the number of missing teeth (≥15 teeth) was positively associated with the occurrence of new-onset diabetes (hazard ratio = 1.21; 95% CI, 1.09–1.33) among 188,013 Korean adults [ 26 ]. This was consistent with our findings that individuals with an increasing number of remaining teeth tended to have lower odds of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our study could not control for the effects of the unmeasured factors. These include the effects of oral factors (e.g., periodontal disease, denture use, and brushing teeth) on the relationship between oral health and sarcopenia or diabetes [ 14 , 26 , 36 ]. Thus, future longitudinal studies are essential for investigating these associations.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of toothbrushing per day is a major variable representing the oral health behavior of an individual, which is not only a powerful factor influencing oral diseases, but is also closely associated with health risk behaviors [10,11]. According to a recent study conducted by Lee and Song [12], the risk of diabetes was increased in the group with periodontal disease and the group with high tooth loss, whereas the risk of diabetes was decreased in the group that received regular teeth scaling. Periodontal disease is also known to increase cerebrovascular disease, atherosclerosis, and premature birth [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with individuals lost no more than three teeth, participants lost more than 15 teeth showed no signi cant difference in incidence of hypertension, which was partly consistent with our pooled analysis. Therefore, though several studies showed that tooth loss might act as a predictor for diabetes [28,29] and metabolic syndrome [30] , there is still no comprehensive evidence for the effectiveness of tooth loss as a predicator of incident hypertension. However, our result didn't repudiate the possibility that after the number of tooth loss exceed a certain number, the incidence of hypertension might increase.…”
Section: The Effectiveness Of Tooth Loss As a Predicator Of Incident mentioning
confidence: 99%